1997
DOI: 10.1111/j.1745-4573.1997.tb00731.x
|View full text |Cite
|
Sign up to set email alerts
|

COLOR AND OXIDATIVE PROPERTIES OF IRRADIATED GROUND BEEF PATTIES1

Abstract: The effects of two doses (2.0 and 3.5 kGy) of nonradioactive irradiation on color and oxidative properties were determined and compared to nonirradiated controls for frozen, raw and precooked, ground beef patties with 10 and 22% fat packaged in vacuum and aerobically. Irradiated raw patties were initially darker and less red than controls, but color of control and irradiated samples became more similar during display. Irradiation increased external redness in precooked patties that were vacuum‐packaged. Aerobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 19 publications
3
14
0
Order By: Relevance
“…However, a* values of beef irradiated at higher doses were lower than the unirradiated control or 1.5 kGy irradiated samples. These results confirmed Luchsinger et al (1997b), who reported that AP beef patties irradiated at 2.0 kGy were less red than the unirradiated control. The a* values for turkey were not different (PϾ0.05) as irradiation dose increased from 0 kGy to 10.5 kGy.…”
Section: Instrumental Color Measurementssupporting
confidence: 94%
“…However, a* values of beef irradiated at higher doses were lower than the unirradiated control or 1.5 kGy irradiated samples. These results confirmed Luchsinger et al (1997b), who reported that AP beef patties irradiated at 2.0 kGy were less red than the unirradiated control. The a* values for turkey were not different (PϾ0.05) as irradiation dose increased from 0 kGy to 10.5 kGy.…”
Section: Instrumental Color Measurementssupporting
confidence: 94%
“…This relationship was maintained through 14 days. Similar results have been reported in other studies in that no differences occurred between irradiated and nonirradiated samples with respect to yellowness (Luchsinger et al. 1997a,b; Nanke et al.…”
Section: Resultssupporting
confidence: 91%
“…(1997a) found that doses of 2.0 or 3.5 kGy had no effect on lightness of whole beef muscle during chilled storage. In another study, irradiation had no effect on L * values of vacuum‐packaged ground beef patties stored for up to 21 days (Luchsinger et al. 1997b).…”
Section: Resultsmentioning
confidence: 99%
“…Zhu, Mendonca, and Ahn (2004) reported that when the loin chops were vacuum packaged, minimal irradiation and temperature Xuctuation eVects on TBARS were expected. Luchsinger et al (1997) reported that TBARS of aerobically packaged ground beef patties increased as irradiation dose increased while those of vacuum packaged sample decreased.…”
Section: Lipid Oxidationmentioning
confidence: 97%